(untitled) (International Journal of Social Research & Innovation, 2019)
This paper presents an in-depth study of the livelihood practices and development needs of one isolated rural island community in the Maldives. The research identified key stakeholders concerns about opportunities and barriers to livelihood practices and community development using a case study approach. Some of the challenges networking locally and nationally to achieving community objectives for food security, water and other resources management, socio-economic development and environmental protec on are identified, followed by strategies to reduce vulnerability in the context of climate change and to develop a sustainable ecosystem for future generations.